Spirala znanja - nova paradigma prenosa znanja v zdravstveni negi - Kaučič, Boris Miha (Obzornik zdravstvene nege, 2005)
The present article presents the spiral of knowledge as a modern model of organizational learning. A practical case of a nurse in an organizational unitis also presented. Knowledge itself is not sufficient, it has to be passedon to the others. In such a way, new quality is acquired, but one shouldbe also able to use the acquired knowledge. Organizational learning alsoincludes the ability to react to the changes in the environment and the ability to solve problems and difficulties and represents an indispensable element and tool which enables an organization to survive in its environment. lt is a dynamic process of creation, acquisition and distribution of knowledge.
Keywords: Education, Nursing, Continuing; Izobraževanje, zdravstvena nega nadaljevalno; knowledge; learning; medicinske sestre; Nursing Care; učenje; Zdravstvena nega; znanje